"Pociąg staje się niby nieskończony...". Podróż pociągiem w poemacie "Dwanaście stacji" Tomasza Różyckiego - Andrzejak-Nowara, Małgorzata; Paluch, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Tomasz Różycki's "Twelve Stations" is a story full of warmth about a generation of migrants from the Eastern Borderlands living in Opole. This generation failed to assimilate to the new reality, therefore they live in a certain isolation. The younger generation either stayed here or moved to the West. The elderly, being unable to find their place, set off back to the Borderlands, although it is only a mental journey.
Keywords: pociągi; wagon; przedział; stacje kolejowe; podróż; droga; ruch; labirynt; rozjazd; zesłanie; wywózka; przesiedleńcy; przekraczanie śmierci; trauma; tymczasowość; utracony raj; trains; wagons; compartments; stations; travel; road; traffic; maze; junctions; exile; deportation; disposals; exceeding death; migrants; temporariness; lost paradise